The Development and Validation of a Novel Nanobody-Based Competitive ELISA for the Detection of Foot and Mouth Disease 3ABC Antibodies in Cattle - Gelkop, Sigal; Sobarzo, Ariel; Brangel, Polina; Vincke, Cécile; Romão, Ema; Fedida-Metula, Shlomit; Strom, Nick; Ataliba, Irene; Mwiine, Frank Norbet; Ochwo, Sylvester; Velazquez-Salinas, Lauro; McKendry, Rachel A.; et al. (Frontiers in Veterinary Science, 2018)
Effective management of foot and mouth disease (FMD) requires diagnostic tests to distinguish between infected and vaccinated animals (DIVA). To address this need, several enzyme-linked immunosorbent assay (ELISA) platforms have been developed, however, these tests vary in their sensitivity and specificity and are very expensive for developing countries. Camelid-derived single-domain antibodies fragments so-called Nanobodies, have demonstrated great efficacy for the development of serological diagnostics. This study describes the development of a novel Nanobody based FMD 3ABC competitive ELISA, for the serological detection of antibodies against FMD Non-Structural Proteins (NSP) in Uganda cattle herds. This in-house ELISA was validated using more than 600 serums from different Uganda districts, and virus serotype specificities. The evaluation of the performance of the assay demonstrated high diagnostic sensitivity and specificity of 94% (95 % CI: 88.9–97.2) and 97.67 % (95 % CI: 94.15–99.36) respectively, as well as the capability to detect NSP-specific antibodies against multiple FMD serotype infections. In comparison with the commercial PrioCHECK FMDV NSP-FMD test, there was a strong concordance and high agreement in the performance of the two tests, with a kappa coefficient of 0.875. This new developed Nanobody based FMD 3ABC competitive ELISA could clearly benefit routine disease diagnosis, the establishment of disease-free zones, and the improvement of FMD management and control in endemically complex environments, such as those found in Africa.